(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Yablonckaya T. Аbout role perspective in the strategy of future-teachers-philologists’ pedagogical training quality raising. The theoretical ground of the role perspective as the main idea of the strategy of future teachers-philologists’ pedagogical training quality raising, its essence and the ways of realization in the teaching process are discovered.